2010
DOI: 10.1353/sls.0.0038
|View full text |Cite
|
Sign up to set email alerts
|

Views, Knowledge, and Beliefs about Genetics and Genetic Counseling among Deaf People

Abstract: Genetic counseling is part of the social response to the science of genetics. It is intended to help twenty-first-century societies manage the consequences of our ability to observe and intervene in our genetic makeup. This article explores the views, knowledge, and beliefs of some Deaf and hard of hearing people about genetics and genetic counseling. Deaf adults are often interested in knowing why they are deaf and whether deafness can be passed on to their children. They may also be interested in knowing abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…72,85 Providing genetic services in a linguistically and culturally sensitive manner has been shown to improve outcomes such as genetics knowledge and understanding. 86,87 Furthermore, using neutral or balanced terminology, such as "chance" instead of "risk, " "deaf " or "hearing" instead of "affected" or "unaffected, " and exercising caution in the use of terms such as "handicapped, " "pathology, " and "impairment" can enhance the provision of genetic services to deaf and hard-of-hearing individuals and their families. 86,88,89 …”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%
“…72,85 Providing genetic services in a linguistically and culturally sensitive manner has been shown to improve outcomes such as genetics knowledge and understanding. 86,87 Furthermore, using neutral or balanced terminology, such as "chance" instead of "risk, " "deaf " or "hearing" instead of "affected" or "unaffected, " and exercising caution in the use of terms such as "handicapped, " "pathology, " and "impairment" can enhance the provision of genetic services to deaf and hard-of-hearing individuals and their families. 86,88,89 …”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%
“…While a recent study found that deaf individuals may have some familiarity with the concept of genetic counseling (Middleton et al 2010a), there is a paucity of data on the effectiveness of genetic counseling to enhance genetics knowledge outcomes in the deaf and hard-of-hearing population, including the Deaf community.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, however, there has been limited (or few) genetic counseling services tailored specifically for the deaf adult population outside of very unique settings such as Gallaudet University, a U.S. university for deaf students (Arnos, Cunningham, Israel, & Marazita, 1992; Arnos, Israel, & Cunningham, 1991b). Thus, although a number of studies have demonstrated that deaf individuals are interested in learning why they are deaf (Arnos et al, 1991b; Boudreault et al, 2010; Burton, Withrow, Arnos, Kalfoglou, & Pandya, 2006; Martinez, Linden, Schimmenti, & Palmer, 2003; Withrow et al, 2009), it is still the case that few deaf individuals seek genetic counseling or genetic services (Enns, Boudreault, & Palmer, 2010; Middleton, Emery, & Turner, 2010). This study underscores the importance of addressing the determinants of low utilization of genetic services by deaf adults because it provides empirical data that genetic information can enhance psychological well-being among individuals who receive a genetic explanation for why they are deaf.…”
Section: Discussionmentioning
confidence: 99%